A rare case of MRI-induced thermal burn: Clinical implications and safety awareness - Amer Abu-Shanab, MD; Hamzeh Nasr, MD; Ahmed Mohd, MD; Mahmoud Shaweish, MD; Ahmad Abdulraheem, MD; Doantrang Du, MD (Radiology Case Reports)
Magnetic Resonance Imaging (MRI) is a widely used, noninvasive diagnostic tool in clinical practice, with millions of scans performed annually. Despite its safety profile, MRI is associated with several potential side effects, including rare but serious complications such as thermal burns. These burns typically result from the interaction of radiofrequency (RF) energy with conductive materials in contact with the skin, or from improper positioning during the scan. This case report details a 76-year-old female who developed a thermal burn on her left elbow after undergoing an MRI of her right shoulder. The patient initially experienced localized heat, redness, and mild tenderness at the site, which later developed into an open wound, leading to a diagnosis of cellulitis. However, further evaluation revealed the wound to be a stage III burn, likely resulting from RF energy exposure during the MRI procedure. The patient had a history of diabetes, a condition that may have contributed to impaired thermoregulation, increasing her risk for thermal injury. The burn was managed with wound debridement, antibiotics, and regular follow-up care, ultimately healing over an 8-week period. This case underscores the importance of understanding the mechanisms of MRI-induced burns, the need for stringent safety protocols, and the role of postprocedure patient education. It also highlights the potential for delayed diagnosis of MRI-related burns, which can be mistaken for other conditions such as cellulitis. Early recognition and appropriate management are critical to preventing complications and ensuring optimal patient outcomes.